A retrospective study of SPECT/CT scans using SUV measurement of the normal pelvis with Tc-99m methylene diphosphonate - Ruifeng Wang; Xiaoyi Duan; Cong Shen; Dong Han; Junchao Ma; Hulin Wu; Xiaotong Xu; tao Qin; Qiuju Fan; Zhaoguo Zhang; Weihua Shi; Youmin Guo (International Journal of Radiology and Radiation Oncology - Peertechz Publications, 2018)
Objective: This study aimed to perform the quantitative measurement based on the standardized uptake value (SUV) of Tc-99m methylene diphosphonate (MDP) in normal pelvis using a single-photon emission tomography (SPECT)/computed tomography (CT) scanner. Material and Methods: This retrospective study was performed on 31 patients with cancer undergoing bone SPECT/CT scans with 99m Tc-MDP between August and December 2016. SUVmax and SUVmean of the normal pelvis were calculated based on the body weight. SUVmax and SUVmean of the bilateral anterior superior iliac spine, posterior superior iliac spine, facies auricularis ossis ilii, ischial tuberosity, and sacrum were calculated. Further, the correlation of SUVmax and SUVmean of all parts of the pelvis with weight, height, and CT was studied.